Kebijakan Pembangunan Satu Desa Satu Milyar (SDSM) Di Kabupaten Pulau Morotai Tahun 2019 - Fandi Hi Latief (Peneliti.net, 2020)
Development Policy of One Billion Villages (SDSM) in Pulau Morotai Regency. in this study, researchers focus on the issues raised namely the Impact of the One Billion One Village Policy in Kab. Morotai Island. This research program discusses the development policy of one village one budget development program, as well as efforts to examine the factors that are considered in improving the efficiency of one billion village program in the development that develops the village development. In this study, researchers used a qualitative descriptive method. Using data collection techniques of observation, interviews and documentation, while the data analysis techniques used are to reduce data, present data, and collect conclusions and suggestions. The results showed that the SDSM program had positive and negative impacts. The positive impact felt was regarding the examination of development and welfare to the village level, budget negotiations for agriculture, and changes in better rural administration. And the negative effect is the incorporation of SDSM which has significant weaknesses, because it is still weak Top-down. Therefore, synergy of all elements is needed so that SDSM can be recycled to meet the needs of the community in the village.